A method for testing hydrogenation deterioration of a material capable of shortening hydrogenation time

CN117686324BActive Publication Date: 2026-10-30ZHEJIANG BAIMA LAKE LABORATORY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310956767.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2026-10-30
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

[0004]为了解决现有的材料掺氢劣化试验中,充氢手段难以在符合实际掺氢环境的同时,兼顾效率的技术问题,本发明提供了一种可缩短充氢时间的材料掺氢劣化性的实验测试方法

Benefits of technology

本发明在测试材料掺氢劣化性的过程中,采用特定的修正公式将需要测试的掺氢条件转换成试验测试时所用的充氢条件,能够在符合实际材料在工业中所处掺氢环境的同时,缩短充氢时间,从而在确保测试结果符合实际的情况下,提高材料掺氢劣化性的实验测试效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117686324B_ABST
    Figure CN117686324B_ABST
Patent Text Reader

Abstract

The present application relates to hydrogen-doping deterioration testing of materials, and discloses an experimental testing method for hydrogen-doping deterioration of materials, which can shorten hydrogen charging time, comprising the following steps: preparing a test piece from the material to be tested; designing hydrogen charging conditions according to the required hydrogen-doping conditions and correction formula for experimental testing, and charging hydrogen into a sealed container containing the test piece; after hydrogen charging is completed, testing the mechanical properties of the test piece; and evaluating the hydrogen-doping deterioration of the material to be tested under the corresponding hydrogen-doping conditions according to the test results of the mechanical properties of the test piece. In the process of testing the hydrogen-doping deterioration of the material, the specific correction formula is used to convert the hydrogen-doping conditions required for testing into the hydrogen charging conditions used for experimental testing, so that the hydrogen charging time can be shortened while the hydrogen-doping environment of the actual material in the industry is met, thereby improving the experimental testing efficiency of the hydrogen-doping deterioration of the material while ensuring that the test results are consistent with the actual situation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogen doping degradation testing technology for materials, and more particularly to an experimental testing method for hydrogen doping degradation of materials that can shorten the hydrogen charging time. Background Technology

[0002] Hydrogen is a high-calorific-value, environmentally friendly fuel with broad development prospects. Currently, with increasingly tight oil supplies worldwide, hydrogen has begun to emerge as a major alternative energy source, entering industrial production and daily life. Hydrogen transportation mainly includes vehicle transport, ship transport, and pipeline transport. Among these, pipeline transport, with its advantages of long distance and low cost, has become an important mode of hydrogen transportation. The construction of pure hydrogen pipelines is too massive, and the method of transporting hydrogen or a hydrogen-natural gas mixture using existing natural gas pipelines or other fuel pipelines has gained favor in many countries. However, unlike natural gas and other gases, hydrogen is more prone to permeating into the pipeline under high transport pressure, leading to hydrogen embrittlement and gas leaks. If exposed to an open flame, the leaked gas can explode, causing further severe environmental damage and casualties. Therefore, research on the suitability of materials for hydrogen blending environments is crucial for the feasibility of hydrogen-blended pipeline transportation.

[0003] Currently, in experiments analyzing the suitability of metallic materials for hydrogen-doped environments, hydrogen charging before mechanical property testing is crucial. Electrochemical hydrogen charging (e.g., patent CN112945660A) and high-pressure hydrogen-doped environment hydrogen charging (e.g., patent CN114383945A) are commonly used methods. Generally, traditional electrochemical hydrogen charging methods are effective, but they do not fully reflect the actual hydrogen-doped environments of metallic materials in industrial settings. While high-pressure hydrogen-doped environment hydrogen charging is more realistic, the charging cycle is generally too long, resulting in low experimental testing efficiency. Therefore, it is of great significance to continue developing an experimental testing method for the hydrogen-doped degradation of materials that not only accurately reflects real-world testing but also significantly shortens the experimental testing cycle. Summary of the Invention

[0004] To address the technical challenge of existing hydrogen-doping degradation tests where hydrogen charging methods fail to simultaneously replicate real-world hydrogen-doping environments and maintain efficiency, this invention provides an experimental testing method for the hydrogen-doping degradation of materials that can shorten the charging time. This method significantly improves hydrogen charging efficiency and accurately reflects the actual hydrogen-doping environments materials face in industrial settings.

[0005] The specific technical solution of this invention is as follows: An experimental testing method for the hydrogen doping degradation of materials that can shorten hydrogen charging time includes the following steps: (1) Prepare test specimens from the material to be tested; (2) Based on the hydrogen doping conditions and correction formula required for the experimental test, design the hydrogen charging conditions and charge the sealed container containing the test specimen with hydrogen; the correction formula is as follows: In the formula, t is the time required for hydrogen charging of the corrected specimen, in seconds; t1 is the time required for hydrogen charging of the specimen before correction, in seconds; l is the hydrogen doping ratio controlled by the actual sealed container, in volume percentage, in %; l1 is the hydrogen doping ratio required for experimental testing, in volume percentage, in %; T is the temperature controlled by the actual sealed container, in K; T1 is the temperature required for experimental testing, in K; (3) After hydrogen charging is completed, mechanical property tests are performed on the specimen; (4) Based on the mechanical property test results of the specimen, evaluate the hydrogen doping degradation of the test material under the corresponding hydrogen doping conditions.

[0006] In this invention, a specific correction formula is used to convert the hydrogen doping conditions to be tested into the hydrogen doping conditions used in the experimental test when designing the hydrogen charging conditions. This can better simulate the hydrogen doping environment of actual materials in industry while greatly shortening the hydrogen charging time and improving the hydrogen charging efficiency. Mechanical property tests are then performed on the specimens treated under the above hydrogen charging conditions. The measured data are processed and analyzed to evaluate the hydrogen doping degradation of the material under the corresponding hydrogen doping conditions. This shortens the experimental testing cycle, and the test results can better predict the actual hydrogen doping degradation of the material in the hydrogen doping environment in industry.

[0007] Preferably, in step (3), the mechanical property test is performed by a slow strain rate tensile test to check the notched tensile strength of the test piece.

[0008] Preferably, in step (2), the hydrogen-filled specimens obtained by hydrogen filling according to the hydrogen filling conditions are used as the experimental group, and the unfilled specimens are used as the control group.

[0009] Preferably, step (4) includes the following steps: (4.1) Calculate the hydrogen embrittlement index of the material to be tested according to the following formula: In the formula, and The notched tensile strengths are those of the unfilled and hydrogen-filled specimens, respectively. (4.2) Evaluate the hydrogen doping degradation of the test material under the corresponding hydrogen doping conditions based on the hydrogen embrittlement index.

[0010] The hydrogen embrittlement index is calculated using a specific formula based on the notched tensile strength of the specimen obtained through a slow strain rate tensile test, which can effectively reflect the hydrogen-induced degradation of the material.

[0011] Preferably, the specific process of step (4.2) includes the following steps: when the hydrogen embrittlement index is greater than 20%, it indicates that the corresponding hydrogen doping conditions are dangerous for the material to be tested; when the hydrogen embrittlement index is not greater than 20%, it indicates that the corresponding hydrogen doping conditions are safe for the material to be tested.

[0012] Preferably, in step (2), the modified formula has 10% ≤ l1 ≤ 50%, 293K ≤ T1 ≤ 893K, and t1 ≥ 3600s.

[0013] Preferably, in step (2), the hydrogen charging conditions include hydrogen doping ratio, temperature, and time.

[0014] Preferably, in step (1), the specimen is a round bar specimen with a total length not greater than 76 mm, a test section diameter less than 8 mm, and a fixed port diameter at both ends not less than twice the test end diameter.

[0015] Preferably, during the slow strain rate tensile test, the tensile rate is 10. -4 ~10 -6 mm / min.

[0016] Preferably, the process for obtaining the hydrogen-free test specimen is as follows: nitrogen gas is introduced into a sealed container containing the test specimen, and the temperature and time are controlled to be the same as those for the hydrogen-filled test specimen, with the nitrogen doping ratio being equal to the hydrogen doping ratio.

[0017] Compared with the prior art, the present invention has the following advantages: In the process of testing the hydrogen doping degradation of materials, this invention uses a specific correction formula to convert the hydrogen doping conditions to be tested into the hydrogen charging conditions used in the test. This can shorten the hydrogen charging time while conforming to the actual hydrogen doping environment of materials in industry, thereby improving the experimental testing efficiency of hydrogen doping degradation of materials while ensuring that the test results are consistent with reality. Attached Figure Description

[0018] Figure 1 This is a technical roadmap for the experimental testing method of hydrogen doping degradation of materials according to the present invention.

[0019] Figure 2 This is a dimensional diagram of the specimens used in Example 1 and Comparative Example 1.

[0020] Figure 3 This is a graph showing the results of a slow strain rate tensile test. The data marked on the curve represents the notched tensile strength, i.e., the maximum load reached during the tensile process. Detailed Implementation

[0021] The present invention will be further described below with reference to embodiments.

[0022] General Implementation Examples An experimental testing method for the hydrogen doping degradation of materials that can shorten hydrogen charging time includes the following steps: (1) Prepare test specimens from the material to be tested; (2) Based on the hydrogen doping conditions and correction formula required for the experimental test, design the hydrogen charging conditions and charge the sealed container containing the test specimen with hydrogen; the correction formula is as follows: In the formula, t is the time required for hydrogen charging of the corrected specimen, in seconds; t1 is the time required for hydrogen charging of the specimen before correction, in seconds; l is the hydrogen doping ratio controlled by the actual sealed container, in volume percentage, in %; l1 is the hydrogen doping ratio required for experimental testing, in volume percentage, in %; T is the temperature controlled by the actual sealed container, in K; T1 is the temperature required for experimental testing, in K. (3) After hydrogen charging is completed, mechanical property tests are performed on the specimen; (4) Based on the mechanical property test results of the specimen, evaluate the hydrogen doping degradation of the test material under the corresponding hydrogen doping conditions.

[0023] In one specific implementation, in step (2), the modified formula is 10% ≤ l1 ≤ 50%, 293K ≤ T1 ≤ 893K, and t1 ≥ 3600s.

[0024] In one specific implementation, step (2) includes hydrogen doping ratio, temperature and time.

[0025] As a specific implementation method, in step (2), the hydrogen-filled test specimen obtained by hydrogen filling according to the hydrogen filling conditions is used as the experimental group, and the unfilled test specimen is used as the control group.

[0026] As one specific implementation, the process of obtaining the hydrogen-free test specimen is as follows: nitrogen gas is introduced into a sealed container containing the test specimen, and the temperature and time are controlled to be the same as those for the hydrogen-filled test specimen, with the nitrogen doping ratio being equal to the hydrogen doping ratio.

[0027] In one specific implementation, in step (3), the mechanical property test is performed by a slow strain rate tensile test with a tensile rate of 10. -4 ~10 -6 mm / min, the notched tensile strength of the test specimen.

[0028] In one specific implementation, in step (1), the specimen is a round bar specimen with a total length not greater than 76 mm, a test section diameter less than 8 mm, and a fixed port diameter at both ends not less than twice the test end diameter.

[0029] As one specific implementation method, step (4) includes the following steps: (4.1) Calculate the hydrogen embrittlement index of the material to be tested according to the following formula: In the formula, and The notched tensile strengths are those of the unfilled and hydrogen-filled specimens, respectively. (4.2) Evaluate the hydrogen embrittlement index of the test material under the corresponding hydrogen doping conditions: when the hydrogen embrittlement index is greater than 20%, it indicates that the corresponding hydrogen doping conditions are dangerous for the test material; when the hydrogen embrittlement index is not greater than 20%, it indicates that the corresponding hydrogen doping conditions are safe for the test material.

[0030] Example 1 The hydrogen doping degradation of No. 20 steel was tested under specific hydrogen doping conditions (hydrogen charging time of 360,000 s, hydrogen doping ratio of 30%, and ambient temperature of 293 K). The procedure is as follows: Figure 1 As shown, the specific process is as follows: (1) Prepare round bar specimens from the material to be tested (20# steel), with dimensions as follows: Figure 2 As shown, the specimen design for slow strain rate tensile testing is based on standard GB / T 34542. The total length of the specimen is 76 mm, the diameter of the test section is 5 mm, and the diameter of the fixed ports at both ends is 10 mm.

[0031] (2) The hydrogen doping conditions to be tested (original hydrogen charging conditions) are: charging time t1 = 360000s, hydrogen doping ratio l1 = 30% (volume percentage), and ambient temperature T1 = 293K. In order to shorten the hydrogen charging time of the test specimen, the original hydrogen charging conditions are substituted into equation (I) to determine the hydrogen charging conditions used in the experiment (corrected hydrogen charging conditions) as follows: hydrogen doping ratio l = 50% (volume percentage), ambient temperature T = 400K, and charging time t = 208748.2s.

[0032] In the formula, t is the time required for hydrogen charging of the corrected specimen, in seconds; t1 is the time required for hydrogen charging of the specimen before correction, in seconds; l is the hydrogen doping ratio controlled by the actual sealed container, in volume percentage, in %; l1 is the hydrogen doping ratio required for experimental testing, in volume percentage, in %; T is the temperature controlled by the actual sealed container, in K; T1 is the temperature required for experimental testing, in K.

[0033] Take a round bar specimen and place it in a high-pressure reactor. Using the hydrogen charging conditions determined above, charge the high-pressure reactor with hydrogen gas to obtain a hydrogen-charged specimen.

[0034] (3) Take another round bar specimen and put it into the high-pressure reactor. Set the temperature to 400K, the nitrogen filling time to 208748.2s, and the nitrogen doping ratio (volume percentage) to 50%. Fill the high-pressure reactor with nitrogen gas to obtain a hydrogen-free specimen.

[0035] (4) Mechanical property tests were conducted on hydrogen-filled and unfilled specimens using a slow tensile mechanical testing machine at a tensile rate of 10. -5 The speed is steplessly adjustable between mm and min, and the load-displacement data of the specimen is stored on the computer. Experimental results are as follows: Figure 3 As shown, the notched tensile strength of the uncharged hydrogen specimen. Notched tensile strength of hydrogen-filled specimens

[0036] (5) According to formula (II), the hydrogen embrittlement index RNS is calculated to be 8.10%.

[0037] Since RNS is no more than 20%, 20 steel is safe under this hydrogen doping condition.

[0038] Comparative Example 1 The hydrogen-induced degradation of No. 20 steel under specific hydrogen-doping conditions (hydrogen charging time of 360,000 s, hydrogen doping ratio of 30%, and ambient temperature of 293 K) was tested. The specific process is as follows: (1) Prepare round bar specimens from the material to be tested (20# steel), with dimensions as follows: Figure 2 As shown, the specimen design for slow strain rate tensile testing is based on standard GB / T 34542. The total length of the specimen is 76 mm, the diameter of the test section is 5 mm, and the diameter of the fixed ports at both ends is 10 mm.

[0039] (2) Take a round bar specimen and place it in a high-pressure reactor. Set the hydrogen charging time to 360,000 s, the hydrogen doping ratio (volume percentage) to 30%, and the temperature to 293 K. Charge hydrogen into the high-pressure reactor to obtain a hydrogen-charged specimen.

[0040] (3) Mechanical property tests were conducted on hydrogen-filled and unfilled specimens using a slow tensile mechanical testing machine at a tensile rate of 10. -5 The speed is steplessly adjustable between mm and min, and the load-displacement data of the specimen is stored on the computer. Experimental results are as follows: Figure 3 As shown, the notched tensile strength of the hydrogen-filled specimen Notched tensile strength of unfilled hydrogen specimen (obtained in Example 1)

[0041] (5) According to formula (III), the hydrogen embrittlement index RNS is calculated to be 6.38%.

[0042] Since RNS is no more than 20%, 20 steel is safe under this hydrogen doping condition.

[0043] Comparing the results of Example 1 and Comparative Example 1, it can be seen that: Figure 3 In the comparison, the load-deformation curves of Example 1 (high-pressure hydrogen-doped environment hydrogen charging modified by the method of the present invention) and Comparative Example 1 (conventional high-pressure hydrogen-doped environment hydrogen charging) are similar, and the calculated hydrogen embrittlement index differs by only 1.72%. This indicates consistency in the hydrogen-doping degradation test results for the test material under the corresponding hydrogen-doping conditions. Therefore, using the method of the present invention to modify the hydrogen charging conditions can effectively shorten the hydrogen charging time and better simulate the actual hydrogen-doping conditions required for testing, resulting in highly accurate test results.

[0044] Unless otherwise specified, the raw materials and equipment used in this invention are all commonly used in the field; unless otherwise specified, the methods used in this invention are all conventional methods in the field.

[0045] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, alterations, and equivalent transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. An experimental testing method for the hydrogen doping degradation of materials that can shorten hydrogen charging time, characterized in that, Includes the following steps: (1) Prepare test specimens from the material to be tested; (2) Based on the hydrogen doping conditions and correction formula required for the experimental test, design the hydrogen charging conditions and charge the sealed container containing the test specimen with hydrogen; the correction formula is as follows: , In the formula, t The time required for the corrected specimen to be charged with hydrogen, expressed in seconds; t 1 represents the time required for hydrogen charging of the specimen before correction, in seconds; l The hydrogen doping ratio is the actual controlled ratio in a closed container, expressed as a volume percentage (%). l 1 represents the hydrogen doping ratio required for the experimental test, expressed as a volume percentage (%). T The actual temperature controlled within the sealed container, expressed in Kelvin (K). T 1 represents the temperature required for the experimental test, in Kelvin (K). (3) After hydrogen charging is completed, mechanical property tests are performed on the specimens; (4) Based on the mechanical property test results of the specimen, evaluate the hydrogen doping degradation of the test material under the corresponding hydrogen doping conditions.

2. The experimental testing method as described in claim 1, characterized in that, In step (3), the mechanical property test is to test the notched tensile strength of the test piece by a slow strain rate tensile test.

3. The experimental testing method as described in claim 2, characterized in that, In step (2), the hydrogen-filled specimens obtained by hydrogen filling according to the hydrogen filling conditions are used as the experimental group, and the unfilled specimens are used as the control group.

4. The experimental testing method as described in claim 3, characterized in that, The specific process of step (4) includes the following steps: (4.1) Calculate the hydrogen embrittlement index of the material to be tested according to the following formula: , In the formula, and The notched tensile strengths are those of the unfilled and hydrogen-filled specimens, respectively. (4.2) Evaluate the hydrogen doping degradation of the test material under the corresponding hydrogen doping conditions based on the hydrogen embrittlement index.

5. The experimental testing method as described in claim 4, characterized in that, The specific process of step (4.2) includes the following steps: when the hydrogen embrittlement index is greater than 20%, it indicates that the corresponding hydrogen doping conditions are dangerous for the material to be tested; when the hydrogen embrittlement index is not greater than 20%, it indicates that the corresponding hydrogen doping conditions are safe for the material to be tested.

6. The experimental testing method as described in claim 1, characterized in that, In step (2), in the correction formula, 10% ≤ l 1≤50%, 293K≤ T 1≤893K, t 1≥3600s.

7. The experimental testing method as described in claim 1, characterized in that, In step (2), the hydrogen charging conditions include the hydrogen doping ratio, temperature, and time.

8. The experimental testing method as described in claim 2, characterized in that, In step (1), the specimen is a round bar specimen with a total length not greater than 76 mm, a test section diameter less than 8 mm, and a fixed port diameter at both ends not less than twice the test end diameter.

9. The experimental testing method as described in claim 2, characterized in that, During the slow strain rate tensile test, the tensile rate was 10... -6 ~10 -4 mm / min.

10. The experimental testing method as described in claim 3, characterized in that, The process of obtaining the hydrogen-free specimen is as follows: nitrogen gas is introduced into a sealed container containing the specimen, and the temperature and time are controlled to be the same as those for the hydrogen-filled specimen. The nitrogen doping ratio is equal to the hydrogen doping ratio. The nitrogen doping ratio is a volume percentage, and the unit is %.

Citation Information

Patent Citations

  • High-temperature and high-pressure gas hydrogen charging test device and test method

    CN112051135A

  • High-strength steel and iron material stress corrosion test method

    CN112881117A